FEATURES AND PROSPECTS OF FIGHTING WITH INFLATION IN RUSSIA - S. Y. Petrov; G. N. Sokolova; E. V. Babeshkova (Russian Journal of Economics and Law)
Objective: to analyze problems and specifics of inflation in Russia. Methods: inductive and deductive. Results: the article analyzes the problems and features of inflation in Russia. The characteristic of inflation, the level and causes are given. The dynamics of inflation in Russia (from 2001 till 2013) is analyzed. The most significant factors and processes are determined and analyzed, that determine the level of inflation in the Russian economy. It is shown that the main reasons boosting inflation are high lending rates and annual increase of tariffs of natural monopolies. It is proved that the phenomena and processes that occur in the analyzed period, do not comply with the monetary rule. Measures are proposed to control inflation in the Russian economy. Scientific novelty: new causes of inflation were detected; the Russian specifics of the phenomenon is shown. Practical value: possibility to optimize the measures of state control over the Russian economy.